Boardroom diversity and audit fees: director ethnicity, independence and nationality - Ayoib CHE AHMAD (Audit Financiar, 2016)

(untitled)
This paper investigated the effect of boardroom diversity (herein a composite measure of boardroom ethnic composition, independent and foreign directors) on audit fees in the Nigerian context. A sample of companies listed on the Nigerian stock exchange between 2010 and 2011 was used. The study found that 51% of the sampled companies were ethnically diverse, with about 21% and 49% having foreign directors and independent directors respectively. Further, the results of the panel regression revealed that boardroom diversity had a positive relationship with audit fees. The findings indicate that boardroom diversity enhances board monitoring responsibility and therefore results in an increase in demand for auditors’ effort. The findings of this study have implications for future policy recommendations and formulation because they indicate that boardroom diversity could be a desirable board characteristic that can strengthen the monitoring role of the board.